2020
DOI: 10.1164/rccm.201905-0969oc
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative IFN-γ Release Assay and Tuberculin Skin Test Results to Predict Incident Tuberculosis. A Prospective Cohort Study

Abstract: Rationale: Development of diagnostic tools with improved predictive value for tuberculosis (TB) is a global research priority. Objectives: We evaluated whether implementing higher diagnostic thresholds than currently recommended for QuantiFERON Gold-in-Tube (QFT-GIT), T-SPOT.TB, and the tuberculin skin test (TST) might improve prediction of incident TB. Methods: Follow-up of a UK cohort of 9,610 adult TB contacts and recent migrants was extended by relinkage to national TB surveillance records (median follow-u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
25
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(28 citation statements)
references
References 26 publications
1
25
0
2
Order By: Relevance
“…Indeed, BALF levels of sCD14, IL-17 and IL-22 all rise in other lung infectious diseases [25,27,28], concordant to sCD14 as a general receptor of LPS and IL-17 and IL-22 as general mediators of T helper 17 cells. Though IGRA can help us to differentiate PTB from non-PTB, it still a pity for these biomarkers could not be diagnostic markers of TB since there were a few IGRA-negative patients with positive results of Xpert test or Mtb culture as reported [29,30]. However, the levels of sCD14, IL-17 and IL-22 re ect the activity of in ammation.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, BALF levels of sCD14, IL-17 and IL-22 all rise in other lung infectious diseases [25,27,28], concordant to sCD14 as a general receptor of LPS and IL-17 and IL-22 as general mediators of T helper 17 cells. Though IGRA can help us to differentiate PTB from non-PTB, it still a pity for these biomarkers could not be diagnostic markers of TB since there were a few IGRA-negative patients with positive results of Xpert test or Mtb culture as reported [29,30]. However, the levels of sCD14, IL-17 and IL-22 re ect the activity of in ammation.…”
Section: Discussionmentioning
confidence: 99%
“…By incorporating a quantitative measure of immunosensitization to M.tuberculosis, we facilitate a shift from the conventional paradigm of LTBI as a binary diagnosis, towards personalized risk stratification for progressive TB. This approach takes advantage of stronger T cell responses being a correlate of risk, while guarding against a loss of sensitivity by arbitrarily introducing higher test thresholds programmatically 16 .…”
Section: Discussionmentioning
confidence: 99%
“…Multiple studies have shown that the magnitude of the T cell response to M.tuberculosis is associated with incident TB risk, raising hope that quantitative tuberculin skin test (TST) or interferon gamma release assay (IGRA) results may improve predictive ability 14,15 . However, implementing higher diagnostic thresholds alone does not improve prediction on a population level due to a marked loss of sensitivity with this approach 16 .…”
Section: Introductionmentioning
confidence: 99%
“…Oman is considering introducing screening of the migrant population from high TB endemic countries for LTBI. The tools available for this screening are the interferon-gamma release assay (IGRA) and tuberculin skin test (TST), both of which detect immunological memory from previous exposure to TB (Goletti et al, 2018;Gupta et al, 2019).…”
Section: Introductionmentioning
confidence: 99%